Unlock Your Career Potential: Interactive Workshop on Job Interview Skills: Penelitian - Vivi Ayu Lestari; Ahmad Najib Mutawally; Arif Budimansyah Purba; Wafiqah Yasmin; Anwar Hilman; Wahyudi; Ludovikus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In today's competitive job market, many students and recent graduates face significant challenges in securing employment, particularly when it comes to mastering interview skills. Research shows that a large percentage of job seekers feel unprepared for interviews, often struggling with communication and confidence. The rise of virtual interviews has further complicated this process, introducing new dynamics that candidates must navigate, such as technical issues and effective online presence.Additionally, employers increasingly use behavioral questions to assess candidates, which can leave many feeling uncertain about how to respond effectively. To address these challenges, we propose the "Unlock Your Career Potential: Interactive Workshop on Job Interview Skills." This workshop will provide participants with essential strategies for understanding the interview process, preparing effectively, and communicating confidently. Through interactive training, mock interviews, and feedback sessions, attendees will gain the skills and confidence necessary to excel in interviews and enhance their employability.